2022
DOI: 10.14704/nq.2022.20.4.nq22258
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Blood Parameters and Platelet-Rich Fibrin Membrane Size for Ocular Graft

Abstract: Purpose: To investigate the relationship between blood parameters and platelet-rich fibrin (PRF) membrane size for ocular graft. Methods: Total of 12 New Zealand white rabbits, 6.5 ml of blood samples was taken for each rabbit, including 5 ml for platelet-rich fibrin membrane production using L-PRF protocol (centrifugation at 2700 rpm for 12 minutes) 1.5 ml for evaluation of blood parameters. Measurement of blood parameters consists of fibrinogen, haemoglobin, hematocrit, red blood cell (RBC), white blood cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…An animal model study observed, using a linear regression analysis, a significant positive effect on the PRF membrane area on the fibrinogen (Pearson correlation coefficient [r] = 0.802; p = 0.02), WBCs (r = 0.625; p = 0.03), and platelets (r = 0.839; p = 0.001). However, there was no apparent correlation between haemoglobin (r = 0.514; p = 0.087), RBCs (r = 0.548; p = 0.065), and haematocrit (r = 0.454; p = 0.138) [60]. Miron et al [61] observed in vivo a larger PRF membrane size in women and patients older than 65 years due to higher haematocrit counts in these patients.…”
Section: Discussionmentioning
confidence: 94%
“…An animal model study observed, using a linear regression analysis, a significant positive effect on the PRF membrane area on the fibrinogen (Pearson correlation coefficient [r] = 0.802; p = 0.02), WBCs (r = 0.625; p = 0.03), and platelets (r = 0.839; p = 0.001). However, there was no apparent correlation between haemoglobin (r = 0.514; p = 0.087), RBCs (r = 0.548; p = 0.065), and haematocrit (r = 0.454; p = 0.138) [60]. Miron et al [61] observed in vivo a larger PRF membrane size in women and patients older than 65 years due to higher haematocrit counts in these patients.…”
Section: Discussionmentioning
confidence: 94%
“…1,7 Platelet-rich fibrin membrane (PRF) is a second-generation platelet concentrate developed by Choukroun et al from France, which is widely used in oral and maxillofacial, plastic surgery, orthopedic and ophthalmic surgery. 8 The PRF membrane has a mechanical function as a framework for cell proliferation, differentiation, and migration that is important for tissue regeneration. The PRF membrane also contains many growth factors that are important in the wound healing process, such as transforming…”
Section: Introductionmentioning
confidence: 99%